(untitled) (Journal of history, 2025)
Currently, in domestic historical science, the personification of historical events and phenomena through the scientific biography of individual historical figures is of great scientific and cognitive importance in actualizing the history of the Fatherland. The identification of the personality traits, personal qualities and morals of historical figures, their influence on socio-political development allows us to assess the Golden place and role played by them from historical memory. Then we know that the study of the activities and work of a person recognized at the national state level reveals the history of the country and the development of society from a new angle. The main purpose of the research is to analyze the historiography of the history of his socio-political activity, personifying Uzbekali Zhanibekov, a well-known state and public figure in the history of the country, a scientist-historian and ethnologist. In accordance with this, the topic implements the tasks of scientific restoration of the biography of a scientist-figure on a factual basis, determination of methodological positions in the study of socio-political activities. The peculiarity of the research methodology is that together with all-scientific methods, the scientific possibilities of a biographical approach in the direction of modern historical personality studies were used. In addition, the socio-political, scientific and creative activities of U. Zhanibekov, recognized as a state and public figure, historian-ethnographer, cultural scientist and sympathizer of the spirituality of the nation, were evaluated according to the criteria of historical personality studies. The scientific result of the study was a scientific restoration of the personal history, socio-political activity and creativity of the scientist-figure on the basis of poststructural scientific principles and principles of independent historical knowledge. The results of the study are considered new in the field of historical personality studies and are distinguished by their applicability, which can serve as methodological support material for teaching the history of the Fatherland.